Influence of oxidation treatment on the corrosion behaviour of Ti-6AI-4V alloy - Chetty, Aloshan Shaun (Department of Mechanical Engineering, 2014)
Titanium-6Al-4V is a greatly desired alloy due to its attractive properties and exceptional corrosion resistance. Surface modifications such as thermal oxidation (TO) and oxygen boost diffusion hardening (OBDH) improve the tribological properties and wear resistance of Ti-6Al-4V. However, surface modification influences the corrosion behaviour of the metal. Therefore, the aim of this research project is to characterize how surface modifications influence the electrochemical behaviour of Ti-6Al-4V.